Delivery Induced Intraperitoneal Rupture of a Cystic Ovarian Teratoma and Associated Chronic Chemical Peritonitis - Reine Nader; Thibault Thubert; Xavier Deffieux; Jocelyne de Laveaucoupet; Guillaume Ssi-Yan-Kai (Case Reports in Radiology)
Intraperitoneal rupture of cystic ovarian teratoma is a rare complication. We report a case in a 29-year-old female, with increased abdominal circumference 2 months after vaginal delivery. MRI/CT raised this diagnosis associated to chemical peritonitis. A malignant ovarian mass with peritoneal carcinomatosis was excluded. Laparoscopic oophorectomy was performed and histologic analysis confirmed imaging findings. This case demonstrates the interest of imaging before surgery in pelvic masses to avoid misdiagnosing and to provide adequate treatment.